Description of Neoholothele gen. nov (Araneae, Theraphosidae, Schismatothelinae) - Guadanucci, Jose Paulo Leite [UNESP]; Weinmann, Dirk (Taylor & Francis Ltd, 2015)
The new genus Neoholothele is herein described based on the results of a recent phylogenetic analysis. This phylogeny, which included representatives of all Theraphosidae subfamilies, showed that the genus Holothele, as hitherto defined, does not comprise a monophyletic group. Neoholothele gen. nov. is diagnosed by the following features: males and females with dark carapace and golden cephalic region; females with striped color pattern on the abdomen dorsum and long and slender spermathecae receptacula; males with retrolateral branch of male tibial spur with apical end wider than proximal end (synapomorphy), with two apical spines. It comprises two species: N. incei (F. O. Pickard-Cambridge, 1898) comb. nov. and N. fasciaaurinigra sp. nov., both from northern South America.
Keywords: Holothele; spider taxonomy; northern South America; tarantula